The Impact of Digital Leadership Competencies on Strategic Performance in Sports Institutions in the United Arab Emirates - Omar Abdelrahman Hassan AlAli; Aymen Haweni; Maher Mrayah (Technium Social Sciences Journal, 2025)
The rapid acceleration of digital transformation has profoundly altered leadership models across various sectors, including sports. In alignment with the United Arab Emirates’ national visions—UAE Vision 2021 and Centennial Vision 2071—this study examines how digital leadership competencies influence strategic performance within sports institutions. The research employed a descriptive-analytical cross-sectional design involving 337 administrators and managerial staff from public and private sports institutions across the UAE. Data were collected using validated instruments that measured digital readiness, leadership competencies, and perceived institutional challenges. Statistical analyses revealed a strong positive correlation between digital leadership competencies, particularly strategic vision, innovation facilitation, and data-driven decision-making—and strategic performance outcomes. Moreover, organizational culture and digital infrastructure emerged as key enablers of leadership effectiveness, while limitations in digital talent development and resistance to change were reported as significant barriers. These findings underscore the necessity of strategic investments in leadership capacity-building, technological infrastructure, and digital culture to advance sustainable performance in the UAE’s sports sector.